"I Wish I Could Have Been With You": Imagining Digital Tenderness in 2 Lizards. (2nd July 2020) - Nelson, Hilde
Abstract : The COVID-19 pandemic has profoundly reframed our ability to connect in bodily, physical ways, prompting a retreat to the digital. Artist Meriem Bennani and filmmaker Orian Barki offer a vessel for this escape in their series 2 Lizards, released in eight episodes in the early stages of the pandemic. Set in a New York populated by animal surrogates, the animated series showcases the eponymous lizards – voiced by Bennani and Barki – navigating the anxiety, boredom, and catharsis of the ensuing quarantine in New York, replete with Zoom birthdays, rooftop concerts, and protests against racial inequity. The series strives to provide a sense of digital tenderness through its inherent hybridity. The lizards, cyborg avatars melding the human, the animal, and the machine, elude binaries and strictures, presenting a new way of forging connection and probing the emotional contours of life in the pandemic. Native to Instagram and created with a wide circle of collaborators, friends, and family, 2 Lizards relishes the elision between online and offline and the liberatory potential of the in-between. Bennani and Barki propose that through the Internet, there are new possibilities for communion, touch, presence, and care when bodies remain contingent and vulnerable. To be animals, they suggest, is to radically reimagine what constitutes the stuff of human experience.